Development of design structure matrix of product architecture case study: multi purpose CNC router - Hilmy, Irfan; Adesta, Erry Yulian Triblas; Samsul Bahrim, Nur’atiyah Najwa; Aini Nurrasyidah, Azhar; Mohd Shahar, Siti Fatimah (2014)
In developing any engineering product, it is crucial to develop product architecture of the system. An engineering team who responsible in developing different module should work together in order to obtain product architecture as a blueprint of the project. It is common to breakdown system or product into smaller elements as follows: subsystems, modules and component and define the interactions between components and subsystems. In order to achieve the performance of the system as a whole, these elements must be integrated to work together. One of the method to develop product architecture is Design Structure Matrix (DSM). The use of DSM for Development of Product architecture with case study a CNC router platform is presented. Using DSM, order of product development can be optimized and any form of wastes can be eliminated in the design stage.